Leader-following Formation Control of Second-order Autonomous Unmanned Systems under Switching Topologies - Soni S.K.; Sachan A.; Kamal S.; Ghosh S.; Djemai M. (My University, 2025)
A distributed formation control is proposed for the leader-following problem of second-order autonomous unmanned systems (AUSs) under switching topologies. A leader dynamics is assumed to be time-varying. Considering practical situations, the kinematic equations are established for the AUSs. Sufficient conditions are provided, which confirms the desired formation of AUSs. The construction of the formation controller is roughly divided in two steps. Firstly, the formation of all follower agents are derived for AUSs. Secondly, the velocity consensus of all follower agents to achieve the desired velocity by ensuring the formation control of AUSs. Finally, a numerical example demonstrates the efficacy of the proposed theoretical results. © 2021 The Society of Instrument and Control Engineers-SICE.